INFORMATION SYSTEM OF MONITORING THE CONDITION OF VEHICLES UNDER ITS CONDITIONS: A GENERAL APPROACH TO THE FORMATION OF A MORPHOLOGICAL MATRIX (Transport systems and technologies, 2018)
The concept of the information system for monitoring the condition of the vehicle, which combines observation, audit, forecast of the vehicle operation and is based on the use of the morphological matrix, is substantiated. Morphological analysis begins with a certain level of knowledge about the object that is being studied. The need to enumerate all possible alternatives for solving the problem and choosing the most optimal direction requires the researcher to have diverse knowledge from various fields. All this contributes to the improvement of knowledge about the object, is being explored to a new level. In the system under study, for the formation of the basic morphological formula of the information system for monitoring automobiles under operating conditions, several characteristic characteristics of the functional elements — morphological features — were identified for each of which the most comprehensive list of various suitable alternatives (alternatives) had been drawn up. . Thus, a change in the constructive expression of a specific variant of any of the features forms a new scheme. The considered approach allows us to systematically investigate all possible schemes that arise from the laws of structure (morphology), thereby taking into account, besides the known, unusual variants that could be rejected with simple enumeration.
Keywords: information system, morphological matrix, vehicle monitoring